Liposomal Gel of Centella asiatica: Antioxidant Activity and Release Profile - Indriaty, Sulistiorini; Firmansyah, Deni; Utami, Mima Eliestya; Karlina, Nina; Suharyani, Ine; Haidar, Hilal; Safitri, Amanda; Setiawati, Elis (Sciences of Pharmacy, 2025)
Centella asiatica (L.) Urban contains flavonoids and triterpenoids with strong antioxidant activity; however, its topical bioavailability is limited by poor solubility. This study aimed to formulate and evaluate liposomal gel systems containing a 70% ethanol extract of C. asiatica to enhance dermal penetration while preserving antioxidant activity. The extract was incorporated into liposomes using a lecithin–cholesterol ratio of 9:1 and formulated into gels at concentrations of 0.3% (FG1) and 0.5% (FG2). Physicochemical characterization showed mean particle sizes of 119.8 ± 7.21 nm (FG1) and 101.3 ± 6.55 nm (FG2), with polydispersity index values of 0.410 and 0.306, respectively, indicating acceptable vesicle homogeneity across three independent replicates (n = 3). The formulations were physically stable for two weeks at 4 °C but exhibited instability at elevated temperatures. Antioxidant activity evaluated using the DPPH assay yielded IC₅₀ values of 13.87 ± 0.02 µg/mL for FG1 and 13.97 ± 0.06 µg/mL for FG2, which were not significantly different (p > 0.05) from vitamin C (9.16 ± 0.06 µg/mL), indicating preservation of radical-scavenging capacity. In vitro permeation studies using Franz diffusion cells demonstrated cumulative quercetin penetration of 280.86 ± 1.12 µg/cm² for FG1 and 314.40 ± 0.93 µg/cm² for FG2 over 4 h, with FG2 showing significantly higher flux (p < 0.05). Release kinetics followed a zero-order model (R² = 0.9881–0.9914), suggesting controlled release behavior. Overall, liposomal gel formulations show potential for improving topical delivery of C. asiatica without overstating long-term stability or therapeutic superiority.